2012
DOI: 10.1073/pnas.1211132109
|View full text |Cite|
|
Sign up to set email alerts
|

Ion-beam irradiation, gene identification, and marker-assisted breeding in the development of low-cadmium rice

Abstract: Rice (Oryza sativa L.) grain is a major dietary source of cadmium (Cd), which is toxic to humans, but no practical technique exists to substantially reduce Cd contamination. Carbon ion-beam irradiation produced three rice mutants with <0.05 mg Cd·kg −1 in the grain compared with a mean of 1.73 mg Cd·kg −1 in the parent, Koshihikari. We identified the gene responsible for reduced Cd uptake and developed a strategy for marker-assisted selection of low-Cd cultivars. Sequence analysis revealed that these mutants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
314
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 443 publications
(326 citation statements)
references
References 24 publications
9
314
2
1
Order By: Relevance
“…In addition, a lot of key genes have been shown to be involved in Cd detoxification and tolerance in plants. These include ZNT1, OsHMA9, OsNRAMP5, ZntA, CAD2, AtPDR12, AtPDR8, AtATM3, ACBP1, Nramp5, EIN2, and MAN3 (Pence et al, 2000;Sharma et al, 2000;Shiraishi et al, 2000;Lee et al, 2003Lee et al, , 2007Kim et al, 2006Kim et al, , 2007Xiao et al, 2008;Cao et al, 2009;Lin and Aarts, 2012;Sasaki et al, 2012;Ishikawa et al, 2012;Chen et al, 2015). It was also found that Heat shock transcription factor A4a (HsfA4a) confers Cd tolerance by up-regulating MT gene expression in wheat (Triticum aestivum) and rice (Oryza sativa; Shim et al, 2009).…”
mentioning
confidence: 95%
“…In addition, a lot of key genes have been shown to be involved in Cd detoxification and tolerance in plants. These include ZNT1, OsHMA9, OsNRAMP5, ZntA, CAD2, AtPDR12, AtPDR8, AtATM3, ACBP1, Nramp5, EIN2, and MAN3 (Pence et al, 2000;Sharma et al, 2000;Shiraishi et al, 2000;Lee et al, 2003Lee et al, , 2007Kim et al, 2006Kim et al, , 2007Xiao et al, 2008;Cao et al, 2009;Lin and Aarts, 2012;Sasaki et al, 2012;Ishikawa et al, 2012;Chen et al, 2015). It was also found that Heat shock transcription factor A4a (HsfA4a) confers Cd tolerance by up-regulating MT gene expression in wheat (Triticum aestivum) and rice (Oryza sativa; Shim et al, 2009).…”
mentioning
confidence: 95%
“…Heavy-ion irradiation has also been accepted as a powerful mutagen for both forward and reverse genetics. Therefore, studies on biological processes in plants and microbes have been advanced by using heavy-ion irradiation (Hase et al, 2000(Hase et al, , 2006Shitsukawa et al, 2007;Shimada et al, 2009;Yasui et al, 2011;Fujita et al, 2012;Sasaki et al, 2012;Ishikawa et al, 2012;Kazama et al, 2013;Hirano et al, 2013;Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6). In rice, Mn and Cd also share the same transporter, OsNramp5, for the uptake Ishikawa et al, 2012;Sasaki et al, 2012), although HvNramp5 differs from OsNramp5 in terms of expression patterns, tissue localization, and specificity of transport substrate as discussed below.…”
mentioning
confidence: 99%
“…On the other hand, OsNrat1 (OsNramp4) transports trivalent Al ion (Xia et al, 2010) and is required for high Al tolerance in rice roots. Finally, OsNramp5 functions as a major transporter responsible for root Mn and Cd uptake Ishikawa et al, 2012;Sasaki et al, 2012). However, the function of OsNramp2, OsNramp6, and OsNramp7 is unknown.…”
mentioning
confidence: 99%